PERAN MODEL TGT DALAM MENINGKATKAN CAPAIAN BELAJAR IPA DI TINGKAT SATUAN PENDIDIKAN DASAR: STUDI LITERATUR - Damayanti Firdaus, Efrida; Mira Amelia Amri; Adi Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science education, known as IPA in elementary schools, plays a crucial role in honing critical thinking skills along with various other transformative competencies needed in the demanding world of the 21st century. However, there are various obstacles faced in science learning, so that students' achievement in science learning in the learning components that include thinking (cognitive), emotional response (affective), and practical skills (psychomotor) are also affected. The Team Games Tournament (TGT) model has become an alternative to encourage improvement in elementary school students' science learning outcomes. Through a descriptive qualitative approach based on a literature study, this article examines ten recent studies that examine the role of TGT in the cognitive, affective, and psychomotor domains of elementary school science learning. The results of the analysis show that the consistent application of TGT improves students' understanding of science concepts (cognitive), motivation (affective), and cooperation (psychomotor) among students. Thus, the TGT model is recommended as the main model in designing science learning at the elementary level, as well as a foundation for further research and development of innovative models.